2016
DOI: 10.3329/jom.v17i1.30063
|View full text |Cite
|
Sign up to set email alerts
|

Visceral Leishmaniasis Turning into Chronic Liver Disease

Abstract: Kala-azar and chronic liver disease are conditions frequently seen in our country. In some instances, when features of both diseases co-exist, it may pose as a diagnostic dilemma. We intend to report a case here, where presence of such features led to much confusion.J MEDICINE January 2016; 17 (1) : 51-54

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Furthermore, different case reports supported the present study and reported liver dysfunction with the raised value of serum AST, ALT, and bilirubin from VL patients. [14][15][16][17][18][19] Similarly, studies conducted in India and Bangladesh also reported abnormally high liver inflammatory enzymes like ALT, AST, and ALP in VL patients. 6,20 This may be attributed to the levels of particular circulating cytokines during the inflammatory processes observed in active VL disease could be a determinant and consequence of severe liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, different case reports supported the present study and reported liver dysfunction with the raised value of serum AST, ALT, and bilirubin from VL patients. [14][15][16][17][18][19] Similarly, studies conducted in India and Bangladesh also reported abnormally high liver inflammatory enzymes like ALT, AST, and ALP in VL patients. 6,20 This may be attributed to the levels of particular circulating cytokines during the inflammatory processes observed in active VL disease could be a determinant and consequence of severe liver disease.…”
Section: Discussionmentioning
confidence: 99%